2015
DOI: 10.1074/jbc.m115.685362
|View full text |Cite
|
Sign up to set email alerts
|

Two Conserved Cysteine Residues Are Required for the Masculinizing Activity of the Silkworm Masc Protein

Abstract: Background:The functional domains of the silkworm masculinizing protein Masc are unknown. Results: The essential region and residues involved in the masculinizing activity of the Masc protein are identified. Conclusion: Masc functions as the masculinizing protein via its C-terminal region but not two zinc finger domains in the N-terminal region. Significance: Our study suggests the mode of action of the masculinizing protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(100 citation statements)
references
References 25 publications
9
91
0
Order By: Relevance
“…Sumi13-3 females expressed both male- and female-specific splice isoforms of Bmdsx and Imp M (Fig 3B, 3D and 3E), consistent with previous reports in which overexpression of Masc-R in BmN4 cells resulted in the expression of both BmdsxM and Imp M [23,29]. However, it is possible that insertion of the UAS- Masc -R transgene changed the expression pattern of genes located near the insertion site, affecting the expression patterns of sex-determining genes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Sumi13-3 females expressed both male- and female-specific splice isoforms of Bmdsx and Imp M (Fig 3B, 3D and 3E), consistent with previous reports in which overexpression of Masc-R in BmN4 cells resulted in the expression of both BmdsxM and Imp M [23,29]. However, it is possible that insertion of the UAS- Masc -R transgene changed the expression pattern of genes located near the insertion site, affecting the expression patterns of sex-determining genes.…”
Section: Discussionsupporting
confidence: 92%
“…Having demonstrated that expression of the Masc-R gene induces Imp M and BmdsxM in BmN4 cells [29], we next investigated the expression of Imp M and the splicing pattern of Bmdsx in Masc-R /+ females. RT-PCR analysis with cDNAs prepared from day-1 first instar larvae showed that Imp M expression was induced in Masc-R /+ females (Fig 3B).…”
Section: Resultsmentioning
confidence: 99%
“…In characterizing PxyMasc we found that the N‐terminal Masc ‐characteristic CCCH‐tandem zinc finger domains are present, but not included in the genome annotated coding region – probably contributing to the difficulty in correctly identifying this homologue to date. Although previous research into the function of B. mori Masc has shown that these zinc finger domains are not necessary for the masculinizing ability of Masc protein (Katsuma et al ., ) or its dosage compensation effects (Kiuchi et al ., ), they are a common feature of other lepidopteran Masc homologues (Kiuchi et al ., ; Fukui et al ., ; Lee et al ., ) as well as the reported homologue from the brine shrimp Artemia franciscana (Li et al ., ). We also identified an alternatively spliced PxyMasc transcript, which lacked the cysteine‐cysteine domain required for masculinizing activity in B. mori (Katsuma et al ., ), as well as the majority of the coding sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The B. mori Masc amino acid sequence (accession number: AB840788.1) was used as a BLASTp query against the available DBM genome (http://iae.fafu.edu.cn/DBM/). Genes showing significant hits were further searched for evidence of homology to the 304–310 aa region of B. mori Masc, a highly conserved sequence containing a cysteine‐cysteine domain known to be required for masculinizing ability (Katsuma et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation